2018
DOI: 10.1124/jpet.118.252049
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporter 2–Mediated Hepatic Uptake Contributes to the Clearance of High-Permeability–Low-Molecular-Weight Acid and Zwitterion Drugs: Evaluation Using 25 Drugs

Abstract: High-permeability-low-molecular-weight acids/zwitterions [i.e., extended clearance classification system class 1A (ECCS 1A) drugs] are considered to be cleared by metabolism with a minimal role of membrane transporters in their hepatic clearance. However, a marked disconnect in the in vitro-in vivo (IVIV) translation of hepatic clearance is often noted for these drugs. Metabolic rates measured using human liver microsomes and primary hepatocytes tend to underpredict. Here, we evaluated the role of organic anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 76 publications
4
62
0
Order By: Relevance
“…In line with our observation, recent reports suggested that organic solute transporter alpha/beta (OSTα/β) expression is considerably upregulated in NAFLD liver, and that N‐linked glycosylation does not influence its trafficking to the plasma membrane and function . The observation that OAT2 expression is decreased significantly in NASH is of interest, as recent studies have shown that its interplay with CYPs impacts the PK of several drugs such as R/S‐warfarin and tolbutamide …”
Section: Discussionsupporting
confidence: 89%
“…In line with our observation, recent reports suggested that organic solute transporter alpha/beta (OSTα/β) expression is considerably upregulated in NAFLD liver, and that N‐linked glycosylation does not influence its trafficking to the plasma membrane and function . The observation that OAT2 expression is decreased significantly in NASH is of interest, as recent studies have shown that its interplay with CYPs impacts the PK of several drugs such as R/S‐warfarin and tolbutamide …”
Section: Discussionsupporting
confidence: 89%
“…Our previous evaluation of transporter-mediated DDIs per ECCS class validated the predominant role of OATPs in the hepatic clearance of class 1B and 3B drugs (Varma et al, 2015(Varma et al, , 2017aEl-Kattan et al, 2016). More recent studies clearly demonstrated OAT2-mediated uptake contribution to the clearance of class 1A drugs (Bi et al, 2018a,b;Kimoto et al, 2018). Additionally, drugs such as sumatriptan, morphine, and ondansetron, which showed association of pharmacokinetic variability with the SLC22A1 genotype, belong to ECCS classes 2 and 4 (Tzvetkov et al, 2013;Matthaei et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Clearly, hepatic clearance of high-MW acids/zwitterions (ECCS class 1B/3B; e.g., statins) is associated with OATP1B1/1B3-mediated hepatic uptake (Shitara et al, 2013;Varma et al, 2015Varma et al, , 2017b. Results of our recent studies have shown that the majority of ECCS class 1A drugs (low-MW acids/zwitterions; e.g., warfarin, tolbutamide) are substrates to OAT2 (Bi et al, 2018b;Kimoto et al, 2018). Similarly, ECCS class 4 drugs (low-permeability bases/neutrals; e.g., metformin) potentially involve OCT1 in their hepatic disposition (El-Kattan and Varma, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Bumetanide is used as probe substrate to estimate the function of MCT6 (Murakami et al, 2005), although it is also a substrate or inhibitor of other transporters in intestinal tissues, such as organic anion transporter 2 (OAT2), sodium-potassium-2chloride cotransporter 1 (NKCC1), multidrug resistance protein 4 (MRP4), and BCRP (Burckhardt, 2012;Tollner et al, 2015;Romermann et al, 2017;Nigam, 2018). Several reports have shown that neither OAT2 nor MRP4 mediate nateglinide transport (Uchida et al, 2007;Kimoto et al, 2018). No evidence has demonstrated that NKCC1 and BCRP mediate nateglinide transport.…”
Section: Discussionmentioning
confidence: 99%